“ШАҲРИЁР” ДОСТОНИДА ТАЪЛИМИЙ - ТАРБИЯВИЙ ҚАРАШЛАРНИНГ АСОСИЙ ЙЎНАЛИШЛАРИ - Алламбергенов, Е.К. (SCIENCE and SOCIETY, 2022)
In the article, one of the unique pedagogical aspects of the "Shahriyor" epic is the issue of moral education. Also, in the article, the idea that the knowledge and education received at school is not enough to achieve the morals in the epic, and the idea that a person should receive education throughout his life as the main criterion in the educational process is emphasized.
Keywords: "Shahriyor" epic; ethnopedagogy; manners; pedagogical guide; education; hard work